Leprosy patients quality of life: a scoping review* - Barcelos, Raissa Mariah Ferraz Moreira; Sousa, Gutembergue Santos de; Almeida, Michelle Veiga de; Palacio, Fabiana Gulin Longhi; Gaíva, Maria Aparecida Munhoz; Ferreira, Silvana Margarida Benevides (Revista da Escola de Enfermagem da USP, 2021)
Objective: To explore the scientific evidence regarding the leprosy patients quality of life. Method: Scoping review according to the Joanna Briggs Institute methodology, with articles indexed in PubMed, Cochrane, LILACS, Embase, CINAHL, Scopus, Web of Science, PsyINFO, INFOLEP, and Google Scholar databases, published in full in Portuguese, English, or Spanish. Results: Seventy-four studies were identified, with 71 of quantitative approach and 3 with a mixed method. There was a predominance of studies published in Brazil (58.1%), with an adult population, (97.3%) and recruited in reference centers for the treatment of leprosy (52.7%). There was greater use of the WHOQOL-bref (50%) and SF-36 (18.9%) instruments to assess quality of life. The study showed that the greatest impairment in quality of life was related to the delay in the diagnosis of the disease, to leprosy reactions, physical disabilities, neuropathic pain, and stigma. Conclusion: Most studies were developed in endemic countries, with adults, and based on observational studies, and the worst scores obtained were associated with physical domain impairment.